The Use of a Novel Moldable Calcium Phosphate Putty (Montage) for Periarticular Fractures: Early Clinical Results. Issue 4 (December 2021) - Atassi, Omar H.; Busel, Gennadiy; De La Fuente, Guadalupe; Donohue, David; Maxson, Benjamin; Shah, Anjan R.; Watson, David T.; Infante, Anthony; Downes, Katheryne; Sanders, Roy W.; Mir, Hassan R.
Abstract : Objective: The objective of this study was to report on the early clinical results of a novel moldable calcium phosphate putty in managing metaphyseal voids associated with periarticular fractures. Design: This was a retrospective cohort study. Setting: Level I Academic Trauma Center. Patients/Participants: A total of 41 patients with periarticular fractures treated from June 2017 to June 2018 were included in the study. Intervention: Open reduction internal fixation. Main Outcome Measurement: Articular subsidence, bone void filler incorporation and resorption, calcium phosphate extravasation into soft tissue and joint, nonunion, infection. Results: Fracture distribution was as follows: 23 plateau, 6 pilon, 5 acetabulum, 4 calcaneus, 1 midfoot, 1 olecranon, 1 distal radius. Twenty-six patients had >6-month follow-up at the time of publication. All fractures have united. There were no instances in which the Montage extravasated into the soft tissue or joint. In all, 23/26 (88%) patients went on to union without articular subsidence. Overall, 25/26 (96%) showed radiographic evidence of incorporation and partial resorption. There were 2 unplanned surgeries (8%). One patient had an open pilon fracture that underwent debridement and implant removal at 4 months for deep infection; 1 patient with a tibial plateau fracture underwent debridement with implant retention at 4 weeks for deep infection. Both went on to clinical and radiographic union. Conclusions: Montage shows excellent efficacy in preventing articular subsidence when used as a metaphyseal void filler with fixation of periarticular fractures. There is strong radiographic evidence of incorporation and partial resorption at early clinical follow-up. The handling characteristics during its application showed no soft tissue or intra-articular extravasation. Early clinical results are promising, and further study is warranted. Level of Evidence: Level IV.